2012
DOI: 10.1104/pp.112.202135
|View full text |Cite
|
Sign up to set email alerts
|

A Bifunctional Enzyme That Has Both Monoacylglycerol Acyltransferase and Acyl Hydrolase Activities    

Abstract: Monoacylglycerol acyltransferase (MGAT) catalyzes the synthesis of diacylglycerol, the precursor of triacylglycerol biosynthesis and an important signaling molecule. Here, we describe the isolation and characterization of the peanut (Arachis hypogaea) MGAT gene. The soluble enzyme utilizes invariant histidine-62 and aspartate-67 residues of the acyltransferase motif for its MGAT activity. A sequence analysis revealed the presence of a hydrolase (GXSXG) motif, and enzyme assays revealed the presence of monoacyl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
23
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(29 citation statements)
references
References 60 publications
3
23
0
Order By: Relevance
“…MAG is converted to DAG by MAG acyltransferase (MGAT) that transfers an acyl moiety from acyl-CoA to MAG. Finally, DAG is then acylated by DAG acyltransferase (DGAT) to produce TAG (Sreedhar, Priya, Sunny, Ram, & Malathi, 2015;Vijayaraj et al, 2012).…”
Section: Identified Proteins From Chia Seedsmentioning
confidence: 99%
“…MAG is converted to DAG by MAG acyltransferase (MGAT) that transfers an acyl moiety from acyl-CoA to MAG. Finally, DAG is then acylated by DAG acyltransferase (DGAT) to produce TAG (Sreedhar, Priya, Sunny, Ram, & Malathi, 2015;Vijayaraj et al, 2012).…”
Section: Identified Proteins From Chia Seedsmentioning
confidence: 99%
“…Vijayaraj et al . () had reported the MAG hydrolase activities of AtMAGL3 (not observed in Table ). Later, AtMAGL3 was known to function as a caffeoyl shikimate esterase (CSE) involved in lignin biosynthesis (Vanholme et al ., ).…”
Section: Discussionmentioning
confidence: 99%
“…The site-directed mutagenesis analysis of Tgl3p (the H298A of HX 4 D motif and the S237A of GXSXG motif) showed that acyltransferase and TAG lipase motifs act independently of each other (Rajakumari and Daum, 2010). Among the 16 AtMAGL members, AtMAGL3, which contains both a HX 4 D acyltransferase motif and a GXSXG lipase motif, was reported to have both MGAT and acyl hydrolase activities (Vijayaraj et al, 2012). When it was analyzed if other AtMAGL members (Yamamoto et al, 2014) and germinating seeds (GS) after 24 h of imbibition.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations